2022
DOI: 10.3390/jcs6010026
|View full text |Cite
|
Sign up to set email alerts
|

Role of Solvent Polarity on Dispersion Quality and Stability of Functionalized Carbon Nanotubes

Abstract: Dispersion of carbon nanotubes (CNT) in solvents and/or polymers is essential to reach the full potential of the CNTs in nanocomposite materials. Dispersion of CNTs is especially challenging due to the van-der-Waals attraction forces between the CNTs, which let them tend to re-bundle and/or re-aggregate. This paper presents a brief analysis of the quality and stability of functionalized multiwalled carbon nanotubes (fMWCNT) dispersion on polar solvents. A comparative study of functionalized CNT dispersion in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…On the contrary, polydispersity occurs in water, with a larger fraction of clusters around d ≈ 100 nm and a mean d ≈ 140 nm. The lower sizes obtained in water are attributed to its polar nature, which contributes to keeping particles separated as observed in other works . SAXS of a 0.025 wt % oil-based nanofluid further indicates that the average particles size composing the larger agglomerate is around D saxs ≈ 28 nm (Figure S1a), in agreement with the SEM estimates of the dry powder.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…On the contrary, polydispersity occurs in water, with a larger fraction of clusters around d ≈ 100 nm and a mean d ≈ 140 nm. The lower sizes obtained in water are attributed to its polar nature, which contributes to keeping particles separated as observed in other works . SAXS of a 0.025 wt % oil-based nanofluid further indicates that the average particles size composing the larger agglomerate is around D saxs ≈ 28 nm (Figure S1a), in agreement with the SEM estimates of the dry powder.…”
Section: Resultssupporting
confidence: 88%
“…The lower sizes obtained in water are attributed to its polar nature, which contributes to keeping particles separated as observed in other works. 49 SAXS of a 0.025 wt % oil-based nanofluid further indicates that the average particles size composing the larger agglomerate is around D saxs ≈ 28 nm (Figure S1a), in agreement with the SEM estimates of the dry powder. It can be concluded that in the oil-based nanofluid, there are TiN nanoclusters with a dimension of around 300 nm, composed of NPs with a diameter of around 30 nm.…”
Section: ■ Results and Discussionsupporting
confidence: 78%
“…[17,[25][26][27] However, to homogeneously disperse the MWCNT, researchers often resort to aggressive polar solvents such as toluene, methanol, and dimethylformamide because they grant a faster and longerlasting dispersion of the nanotubes. [28] In an effort to contradict this tendency, Rajendram et al conducted a study using different solvents, namely water, ethanol, 2-propanol (IPA), and toluene to analyze their influence on the dispersion of MWCNT. [28] According to their findings, the affinity of functionalized MWCNT is higher for water, followed by ethanol, IPA, and finally, toluene.…”
Section: Doi: 101002/adem202400132mentioning
confidence: 99%
“…[29][30][31][32] However, it is worth noting that the poor dispersion of CNT in various solvents causes inhomogeneous mixing with the active material. [29,33,34] To overcome this issue, in this work, CNT is chemically functionalized to create oxygencontaining surface functional groups prior to the in-situ mixing in the aqueous vanadium precursor solution. The water contact angle measurements on the pristine CNT (pCNT, Figure S1a, Supporting Information) and fCNT samples (Figure S1b, Supporting Information) prove that the latter possesses more hydrophilicity than the former.…”
Section: Physical Characterizationmentioning
confidence: 99%
“…For instance, pCNT displays a high water contact angle of 94.1°, whereas the same is extremely low in fCNT due to its excellent wetting behavior, suggesting the importance of the pre-functionalization of CNT. [34] The attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR) measurement of fCNT (Figure S2b, Supporting Information) shows the appearance of the broad peaks at 3050 to 3500, 1630, and 1020 cm −1 related to the presence of the different oxygen functionalities (-OH, -COOH, -C=O, and -C-O) that contribute to its hydrophilic nature and improved dispersion in the aqueous medium (Figure S2a, Supporting Information). [35,36] During the synthesis of VP/fCNT-P composite, these functional groups on fCNTs can electrostatically interact with the VO 2 + ions present in the reaction solution and serve as the anchoring sites for the growth of the VP nanosheets.…”
Section: Physical Characterizationmentioning
confidence: 99%